European societies, migration, and the law: the 'others' amongst 'us' - Jesse, Moritz (Cambridge University Press, 2020)
Not a day passes without political discussion of immigration. Reception of immigrants, their treatment, strategies seeing to their inclusion, management of migration flows, limitation of their numbers, the selection of immigrants; all are ongoing dialogues. European Societies, Migration, and the Law shows that immigrants, regardless of their individual status, their different backgrounds, or their different histories and motivations to move across borders, are often seen as 'the other' to the imaginary society of nationals making up the receiving (nation-)states. This book provides insights into this issue of 'othering' in the field of immigration and asylum law and policy in Europe. It provides an introduction to the mechanisms of 'othering' and reveals strategies and philosophies which lead to the 'othering' of immigrants. It exposes the tools applied in the implementation and application of legislation that separate, deliberately or not, immigrants from the receiving society.